2013
DOI: 10.1155/2013/240537
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol- and/or Taurine-Induced Oxidative Stress in Chick Embryos

Abstract: Because taurine alleviates ethanol- (EtOH-) induced lipid peroxidation and liver damage in rats, we asked whether exogenous taurine could alleviate EtOH-induced oxidative stress in chick embryos. Exogenous EtOH (1.5 mmol/Kg egg or 3 mmol/Kg egg), taurine (4 μmol/Kg egg), or EtOH and taurine (1.5 mmol EtOH and 4 μmol taurine/Kg egg or 3 mmol EtOH and 4 μmol taurine/Kg egg) were injected into fertile chicken eggs during the first three days of embryonic development (E0–2). At 11 days of development (midembryogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Taurine has been added to culture media for its antioxidant properties even though its ability to increase blastocyst formation in humans has not been proven [ 21 ]. A recent study performed in chick embryos even suggested that exogeneous taurine increased brain oxidative stress and apoptosis during embryo development [ 22 ]. Second, glutamine, a deliberately omitted labile amino acid, is supplied in both media by different heat-stable di-peptides (Alanyl-L-Glutamine (AlaGln) in SSM and Glycyl-L-Glutamine (GlyGln) in Global) in order to prevent ammonium production, which has long been known to retard foetal development and cause neural tube defect exencephaly [ 23 ] even after short exposure especially during the cleavage stages [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taurine has been added to culture media for its antioxidant properties even though its ability to increase blastocyst formation in humans has not been proven [ 21 ]. A recent study performed in chick embryos even suggested that exogeneous taurine increased brain oxidative stress and apoptosis during embryo development [ 22 ]. Second, glutamine, a deliberately omitted labile amino acid, is supplied in both media by different heat-stable di-peptides (Alanyl-L-Glutamine (AlaGln) in SSM and Glycyl-L-Glutamine (GlyGln) in Global) in order to prevent ammonium production, which has long been known to retard foetal development and cause neural tube defect exencephaly [ 23 ] even after short exposure especially during the cleavage stages [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cysteamine has a toxicity to bovine embryos and chicken sperm [31,32]. Additionally, taurine supplementation-induced oxidative stress may also depress ovary development [33]. Therefore, depressed ovary development caused by the toxicity of cysteamine and oxidative stress of taurine may explain the depressed egg quality and production performance in hens at the late stage of egg production.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] EtOH treatments during early chick embryogenesis caused decreased brain membrane long-chain polyunsaturated fatty acids (PUFA) levels, decreased brain glutathione (GSH) levels, increased brain homocysteine levels, increased brain lipid hydroperoxide (LPO) levels, and reduced embryo viability as measured by EtOH-induced decreased brain masses and increased brain caspase-3 activities in theoretical stage 37 chick embryos. 9,[11][12][13][14][15] Early embryonic EtOH exposure caused reduced neuron densities within the cerebral hemisphere that correlated with EtOH-induced reductions in brain unsaturated/saturated membrane fatty acid ratios with a correlation coefficient (r) of 0.52 (P < 0.0002) in stage 44 chick embryos. 16 Exogenous α-tocopherol and γ-tocopherol, known antioxidants, attenuated EtOH-reduced brain membrane long-chain PUFA levels and EtOH-induced increased brain LPO levels in stage 44 embryos.…”
Section: Introductionmentioning
confidence: 99%